Study on the revision of SEC rules on auditor independence : a Singapore perspective. - Lee, Clara Ann Meiling. (2008)
This study examines the impact of financial relationships, employment relationships and non-audit services (NAS) on the users’ perception of auditor independence in Singapore and whether the Securities Exchange Commission (SEC) revisions on auditor independence requirements should be implemented in Singapore.